2013
DOI: 10.1111/bjd.12432
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the relapse of infantile haemangiomas in children treated with oral propranolol

Abstract: SummaryBackground Although propranolol has become the first-line therapy for infantile haemangiomas (IHs), no study has yet investigated factors associated with the risk of relapse in children with IH treated with propranolol after cessation of treatment. Objectives To compare factors associated with the risk of relapse in children with IH treated with oral propranolol. Methods We conducted a single-centre retrospective observational study. All files and photographs of patients with IH aged 5 months or less at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
25
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 13 publications
4
25
2
5
Order By: Relevance
“…18 The rate of rebound growth (32%) was consistent with that of previous reports. 18,19 However, the proportion of patients who were judged as requiring retreatment in our study (24%) was higher than in the retrospective studies (15% 19 and 12% 18 of patients required retreatment or modification of systemic therapy) and the pivotal study (10% 13 of patients required retreatment). However, these studies were not restricted to high-risk IH patients only, who are more likely to require treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…18 The rate of rebound growth (32%) was consistent with that of previous reports. 18,19 However, the proportion of patients who were judged as requiring retreatment in our study (24%) was higher than in the retrospective studies (15% 19 and 12% 18 of patients required retreatment or modification of systemic therapy) and the pivotal study (10% 13 of patients required retreatment). However, these studies were not restricted to high-risk IH patients only, who are more likely to require treatment.…”
Section: Discussionsupporting
confidence: 91%
“…13 Therefore, we evaluated the efficacy and safety of oral propranolol in patients with high-risk IH when administered for a minimum of 6 months and up to a maximum of 12 months of age. Furthermore, because rebound growth is reported in ∼25% of patients after stopping propranolol, 18,19 the persistence of IH response and the efficacy of retreatment was evaluated along with the impact of treatment on parents' quality of life (QoL).…”
mentioning
confidence: 99%
“…They also found that children at risk of relapse were mostly those with segmental IH, and those with IH with a deep component. 22 This was very similar to what we found in our series. The percentage of IH that did not respond to the treatment was 4.8% in our series.…”
Section: Discussionsupporting
confidence: 92%
“…Their finding of increased rebound in deep or mixed IH and segmental IH is consistent with other reports, [6][7][8] as is the increased risk of rebound observed in girls 2,[6][7][8] The aforementioned hemangioma subtypes may represent a unique subpopulation of IH programmed to proliferate longer. 11,12 In a series of IH with prolonged growth by Brandling-Bennett et al, 11 all 23 lesions were on the head and neck, another feature found in the current study; in that series, nearly 40% of IH involved the parotid gland, a detail not included in the current report.…”
supporting
confidence: 90%
“…One limitation that has become clearer with accumulating clinical experience, though, is that of potential rebound IH growth after OP, estimated to occur in 6% to 25% of children. 2,[5][6][7][8][9] Understanding the phenomenon of postpropranolol rebound, and being able to predict or (better yet) prevent it, will increase clinical success and parental satisfaction with OP therapy and, in some instances, help prevent morbidity (such as airway blockage resulting from subglottic IH rebound).…”
mentioning
confidence: 99%